Levels of Affixation in the Acquisition of English Morphology: A Review of Selected Paper - Sikin Nuratika; Nilam Cahaya Fitri Yanti; Ester Mayer (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2019)
In considering word formation in language development, there appear to be two central issues which can broadly be characterized as questions relating to (i) productivity, and (ii) constraints. This paper reviews one of the renowned articles which involving the theory of level-ordering that has three levels within the lexicon, children, recognize high-frequency words than low-frequency words written by Peter Gordon (1989), entitled